Long-Term Phase Changes In The South Aral Sea Region Lakes - Farida Y. Artykova; Salauat B. Kalabaev (Водное хозяйство России: проблемы, технологии, управление)
A detailed study of the hydrological regime of lakes is an urgent task, however, it should be noted that this issue is complicated by the lack of systematic observations on lakes. In such cases, satellite images can be used to obtain information about water bodies in hard-to-reach areas. The study carried out mapping of six lakes located in the Southern Aral Sea region. The mapping was carried out for different dates and different phases of the hydrological regime of the lakes in the presence of water in them.